Gastric varices: Classification, endoscopic and ultrasonographic management - Zeeshan Ahmad Wani; Riyaz Ahmad Bhat; Ajeet Singh Bhadoria; Rakhi Maiwall; Ashok Choudhury (Journal of Research in Medical Sciences, 2015)
Gastric varices (GV) are responsible for 10-30% of all variceal hemorrhage. However, they tend to bleed more severely with higher mortality. Around 35-90% rebleed after spontaneous hemostasis. Approximately 50% of patients with cirrhosis of liver harbor gastroesophageal varices. In this review, new treatment modalities in the form of endoscopic treatment options and interventional radiological procedures have been discussed besides discussion on classification and pathophysiology of GV.